Case report: Abscesses in children caused by invasive group A Streptococcus - Guo, Danchun; Zhuang, Shuting; Lu, Qinghua; Chen, Yunsheng; Meng, Qing; Sun, Lifang; Zheng, Yuejie; Wang, Wenjian; Yu, Dingle (Frontiers in Medicine, 2024)
Streptococcus is one of the common pathogens of suppurative infection, invasive group A Streptococcus(GAS) infections often developed from skin or soft tissue infection, and streptococal toxic-shock syndrome was the main cause of death in Chinese children. However, soft tissue infection caused by GAS infection, especially the formation of abscess, is relatively rare. A retrospective study was conducted and pediatric in-patients with GAS infection identified by cultures from normally sterile sites were included, who were diagnosed and treated in a tertiary hospital during 2016-2018. A total 14 patients were identified, in which 10 boys and 4 girls aged from 3 months to 10 years, with soft tissue infection and a diagnosis of abscess caused by GAS. The most common sites of infection were the lower limbs. In five patients, the abscess was accompanied by fever, and the local soft tissue showed redness, swelling, tenderness, and an elevated skin temperature. Laboratory findings included an increased white blood cell count in 12 patients, increased C reactive protein level in 7 patients, and increased erythrocyte sedimentation rate in 10 patients.No patients had an elevated procalcitonin level. All patients were treated by abscess incision and drainage, and GAS was cultured from the drainage fluid. All children also received antibiotic treatment. During 2 months of follow-up, the patients' condition remained stable, and no evidence of kidney or heart damage was observed.For pediatric patients of abscess, early diagnosis, prompt treatment with incision and drainage, and immediate culture of the drainage fluid are important. Upon confirmation of GAS infection, β-lactam antibiotics provide effective treatment, and in some patients with poor therapeutic outcomes, replacement of vancomycin as an alternative can achieve the desired results.